Diet and risk of breast cancer - Kotepui, Manas (Contemporary Oncology/Współczesna Onkologia, 2016)
Diet may play a role in both promoting and inhibiting human breast cancer development. In this review, nutritional risk factors such as consumption of dietary fat, meat, fiber, and alcohol, and intake of phytoestrogen, vitamin D, iron, and folate associated with breast cancer are reviewed. These nutritional factors have a variety of associations with breast cancer risk. Type of fat consumed has different effects on risk of breast cancer: consumption of meat is associated with heterocyclic amine (HCA) exposure; different types of plant fiber have various effects on breast cancer risk; alcohol consumption may increase the risk of breast cancer by producing acetaldehyde and reactive oxygen species (ROS); intake of phytoestrogen may reduce risk of breast cancer through genomic and non-genomic action; vitamin D can reduce the risk of breast cancer by inhibiting the process of cancer invasion and metastasis; intake of dietary iron may lead to oxidative stress, DNA damage, and lipid peroxidation; and lower intake of folate may be linked to a higher risk of breast cancer.